(untitled) (World Bulletin of Social Sciences, 2023)
The possibilities of STEAM technology in elementary school contribute to the expansion of students’ knowledge about being and the world around them. Today, the development of continuous education in our country is being improved, the introduction of international technologies in public education. This article focuses on the importance of STEAM technology in teaching elementary grades